2020
DOI: 10.1007/s40751-020-00061-9
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Reasoning: Digital Task Design to Promote Students’ Conceptions of Graphs as Representing Relationships between Quantities

Abstract: We posit a dual approach to digital task design: to engineer opportunities for students to conceive of graphs as representing relationships between quantities and to foreground students' reasoning and exploration, rather than their answer-finding. Locally integrating Ference Marton's variation theory and Patrick Thompson's theory of quantitative reasoning, we designed digital task sequences, in which students were to create different graphs linked to the same video animations. We report results of a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Results of empirical research provided backing for this approach. Johnson et al (2020) engaged 13 secondary students with the Cannon Man and Toy Car tasks, and found that students discerned critical aspects of graphs themselves, what graphs "should" represent. To illustrate, one student distinguished between a convention, where an attribute was represented in a Cartesian plane (i.e., distance traveled on the vertical axis), and where she imagined that attribute in the physical world (on the ground).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of empirical research provided backing for this approach. Johnson et al (2020) engaged 13 secondary students with the Cannon Man and Toy Car tasks, and found that students discerned critical aspects of graphs themselves, what graphs "should" represent. To illustrate, one student distinguished between a convention, where an attribute was represented in a Cartesian plane (i.e., distance traveled on the vertical axis), and where she imagined that attribute in the physical world (on the ground).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 (Cannon Man) and Figure 2 (Toy Car) show a screenshot of the end of each video animation (dotted lines provide an approximate trace of each object's motion) and computergenerated sketches of the two graphs in each task. For a more detailed description of the tasks, see Johnson et al (2020).…”
Section: Variation Theory In Task Design For Graphs: Different Forms mentioning
confidence: 99%
“…For example, Lingefjärd and Farahani (2017) identified three categories: (1) intuitive and iconic interpretations, (2) scientifically grounded interpretations and (3) a combination with influences from both 1 and 2. Similarly, Johnson et al (2019) included an iconic category and three other categories: motion of objects, individual quantities, and relationship between quantities. Our categories resemble these earlier categorizations.…”
Section: Discussionmentioning
confidence: 99%
“…One is an FLC and a local classroom community. Another is different theoretical communities, because there are different theoretical perspectives informing the design of the techtivites (Johnson et al, 2020). Our use of variation theory (Kullberg et al, 2017;Marton, 2015) underlies our decision to incorporate variation against a background of invariance.…”
Section: The Techtivities: Five Design Principlesmentioning
confidence: 99%
“…Each techtivity has four main elements (Johnson et al, 2020). First, students are to view a video animation and then consider attributes in the animation that may be possible to measure.…”
Section: Elements Of a Techtivitymentioning
confidence: 99%